INTENTIONAL REPLANTATION OF MANDIBULAR FIRST MOLAR WITH TWO YEARS FOLLOW UP- CASE REPORT - Javed, Muhammad Qasim; Zaman, Hira; Srivastava, Swati; khan, zohra Jabeen (Journal of Ayub Medical College Abbottabad, 2022)
Backgrounds: Intentional replantation (IR) is a reliable and predictable treatment option for cases with failed non-surgical root canal treatment. The success of IR is found to be 52-95%. The current case is of 35years old female who presented with severe pain and swelling in lower right first mandibular molar with previously initiated non-surgical root canal treatment that resulted in instrument separation in mesio-buccal canal. Periapical radiograph showed rarefactions at furcation area, mesial and distal root apices. It was decided to complete the non-surgical root canal treatment followed by intentional replantation and retrograde filling with MTA. The tooth was found to be asymptomatic after two years follow up and periapical radiographs depicted complete healing. Intentional replantation with careful case selection is a successful, easy and reliable treatment option for hopeless cases. Atraumatic extraction, minimum extra-alveolar time and aseptic techniques during the procedure are the key factors for success of the procedure.